Association study confirms the role of two OCA2 polymorphisms in normal skin pigmentation variation in East Asian populations. Issue 4 (23rd March 2015) - Eaton, Katherine; Edwards, Melissa; Krithika, S.; Cook, Gillian; Norton, Heather; Parra, Esteban J.
<x xml:space="preserve">Abstract</x> Objectives The main goal of the study was to test the association of 18 polymorphisms located within nine pigmentation candidate genes with quantitative skin pigmentation measures collected in a sample of individuals of East Asian ancestry living in Canada (N = 419). Methods The 18 polymorphisms are located within genes that show putative signatures of positive selection in East Asian populations. The genetic markers were selected for genotyping based on an annotation of common East Asian polymorphisms to predict potential functional effects. We restricted our attention to polymorphisms that have an allele frequency difference of at least 30% between East Asian populations and African and European populations, or have alleles that are present in East Asians, but are absent in Africans and Europeans. Results Two nonsynonymous variants selected within the OCA2 gene, rs1800414 (His615Arg) and rs74653330 (Ala481Thr), were significantly associated with melanin levels in the sample. Both single nucleotide polymorphisms (SNPs) are nonsynonymous polymorphisms located more than 30 kb apart on chromosome 15 and have very different frequencies in the East Asian sample. Additionally, both polymorphisms are predicted to have a deleterious effect on the protein. Linear regression analysis using an additive model indicate that each copy of the derived rs1800414 allele G decreases Melanin Index approximately 0.9 units and each copy of the derived rs74653330 allele A decreases Melanin Index approximately 1.9 units. Conclusions Two nonsynonymous OCA2 polymorphisms (rs1800414 and rs74653330) are independently associated with normal skin pigmentation variation in East Asian populations and have very different frequency distributions in East Asia. Am. J. Hum. Biol. 27:520–525, 2015. © 2015 Wiley Periodicals, Inc.